Problems of the socially disadvantaged child in Colombo: a pilot project - Senanayake, M. P.; Lamabadusuriya, S. P.; Seneviratne, T. (Sri Lanka College of Paediatricians, 2000)
Data on the disadvantaged urban child is meagre. A prospective survey of 60 households in Borella North, each with at least one child under 2 years of age, was carried out over 8 months. The socioeconomic status, the physical environment and the health of the population were investigated. One hundred and ten families lived in the 60 households and 29% of the population were under the age of 5 years. Only a minority of families had regular employment. The source of water was the roadside tap for 70% of households. Solid waste and blocked drains were present in the environment. 80% of homes were over-crowded. Family planning was practised only by 17% of parents. 25% of under fives were in grade 2 protein calorie malnutrition and 20% of this age group needed at least one hospital admission during the study period. We conclude that the disadvantaged urban child has health risks that need multidisciplinary interventions.
Keywords: Socially disadvantaged child; Sri Lanka